Didactic program English for life based on B-learning approach to improve the English Language learning - Ventura Bravo, Ernesto Elías (2018)
The following research is based on the reality that postgraduate students of the institute of languages showed at Lambayeque University. It is also obvious that postgraduate students do not take the English course when they finish their master program because they do not have enough time and they live away from the city because of work. It has been seen when postgrade students took the English course, they were taught in a traditional way and teachers did not use the new methodologies that could be applied in order to improve participation, communication, motivation and students’ performance. The study was conducted to a sample of 30 students who are between 28 and 50 years old. I started the research process through the application of the pre-test to identify the learning level of the English language, then the didactic program “English for life” was applied in order to improve the learning of the language and finally the application of the post-test in order to evaluate the level of improvement in the sample. The type of study is applied, experimental design and with only one group. After the application of the pre-test and post-test, the effectiveness of the didactic program “English for life” was proved and there was a significance improvement in the learning of the English language. The head of the institute of languages was suggested following this new didactic program as an institutional policy in order to have an innovated course for the students of post grade of this university.